Modality Used in Indonesian Presidential Debate: A Corpus-Based Political Discourse Study - Sumari, Binti Aisiah Daning (International Journal of English Education and Linguistics (IJoEEL), 2025)
The language utilized by politicians during electoral debates encompasses linguistic strategies for persuading and influencing their target audiences. Broadcasted on Indonesian televisions in 2023-2024, the presidential candidates articulated their visions and presented persuasive arguments to win over votes. I observed that one of the language principles employed by the candidates in the recent electoral debate to convince prospective voters was linguistic modality. This research scrutinizes the type and function of modality used by these candidates. It is revealed that modality verbs which frequently emerged, such as ‘bisa’ (can), ‘akan’ (will), ‘harus’ (must), ‘ingin’ (want), ‘mungkin’ (may), and ‘mesti’ (should). After being transcribed, all data comprising a total of 40.239-word tokens or 8.982-word types were saved as plain text (.txt). AntConc 4.2.4 Software was used to import data and to automatically generate its frequency, concordance, collocation, and KWIC. The results indicate that epistemic modality is (48%), dynamic modalities (7.32%), intentional modality (11.4%), and deontic modalities (33.28%). The results obtained from this research may offer supplementary insights for discourse analysts and other linguists who have a similar interest in studying modality. This research suggests that politicians are more convincing if they use strong modalities in electoral debates.